Cornwall in the Work of John Betjeman - Zaťko, Michal (Univerzita Pardubice, 2019)
The bachelor thesis is focused on Cornwall described in poems and prose of Sir John Betjeman. It explores author's perception of the local landscape, architecture and elements of topophilia in his works concerning Cornwall. The second half of the paper discovers Betjeman's affective ties to Cornwall, his rejection of modern trends and nostalgia about the past.
Cornwall v díle Johna Betjemana
Keywords: Betjeman, John; Cornwall; krajina; nostalgie; topofilie; Betjeman, John; Cornwall; landscape; nostalgia; topophilia